第54-55次日本南極地域観測隊（JARE-54&-55）におけるアイスフェンスを用いた氷海内海洋観測 - 高橋, 邦夫; タカハシ, クニオ; 高村, 友海; タカムラ, トモミ; 小達, 恒夫; オダテ, ツネオ; Takahashi, Kunio T.; Takamura, Tomomi R.; Odate, Tsuneo (2014)
P(論文) 第52次日本南極地域観測隊より開始した氷海内における海洋生態系モニタリング観測において，観測機器の破損やプランクトン試料へのダメージを抑えるために，測器を海氷からガードする“アイスフェンス”を用いている．これまで一定の成果を挙げてきてはいるが，近年の昭和基地周辺における厳しい氷状においても観測を可能とするために，アイスフェンスの改良を継続した．本報告では第54次隊および第55次隊において実施したアイスフェンスの改良の紹介と，実際の現場における観測の概要について報告する． The marine biological monitoring program in the sea-ice area off Syowa Station was started by the 52nd Japanese Antarctic Research Expedition. The use of an “ice-fence” protected observation equipment (e.g., plankton nets and CTDs) from damage due to sea-ice. However, heavy sea-ice conditions have occurred frequently off Syowa Station in recent years. Therefore, we modified the ice-fence (diameter: 1000mm, height:1200mm, stainless steel) to enable observations under heavy sea-ice conditions. This report describes the results of field tests of the modified ice-fence performed during the 54th and 55th Japanese Antarctic Research Expeditions. departmental bulletin paper